(Semantic web) services for e-learning. (9th October 2008) - Millard, David E.; Doody, Karl; Davis, Hugh C.; Gilbert, Lester; Howard, Yvonne; Tao, Feng; Wills, Gary
Service-Oriented Architectures (SOAs) are becoming a popular system paradigm in e-learning and there are several efforts to create community-driven service frameworks. In this paper, we argue that these efforts could benefit if they also drew on semantic web technologies to create (semantic web) services – services that use the resources described on the semantic web. We present a demonstrator which uses three such services to search over question bank data. We show how the use of semantic web technologies not only promotes high-quality and interoperable metadata, but that it also enables reasoning rules that make developing new services easier to be declared.